2012
DOI: 10.1021/la302613g
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lys147 in the Interaction between MPSA-Gold Nanoparticles and the α-Hemolysin Nanopore

Abstract: Single channel recordings were used to determine the effect of direct electrostatic interactions between sulfonate-coated gold nanoparticles and the constriction of the Staphylococcus aureus α-hemolysin protein channel on the ionic current amplitude. We provide evidence that Lys147 of α-hemolysin can interact with the sulfonate groups at the nanoparticle surface, and these interactions can reversibly block 100% of the residual ionic current. Lys147 is normally involved in a salt bridge with Glu111. The capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 33 publications
2
22
1
Order By: Relevance
“…We find that all three gold nanoclusters can be trapped in the sensing region of a single αHL channel for extended periods and this enables the observation of discrete changes in the current that we associate with ligand rearrangement on the particle. Similar multistep transitions have been reported previously for sulfonate-capped ligands (MPSA), but those fluctuations were assumed to result from Brownian diffusion or binding between the nanocluster ligands and residues in the constriction region of the αHL pore. , Here we show that the multistate fluctuations seen for our particles most likely result from intraparticle rearrangements. We report several experiments and develop a simplified geometric model to support this claim.…”
supporting
confidence: 87%
“…We find that all three gold nanoclusters can be trapped in the sensing region of a single αHL channel for extended periods and this enables the observation of discrete changes in the current that we associate with ligand rearrangement on the particle. Similar multistep transitions have been reported previously for sulfonate-capped ligands (MPSA), but those fluctuations were assumed to result from Brownian diffusion or binding between the nanocluster ligands and residues in the constriction region of the αHL pore. , Here we show that the multistate fluctuations seen for our particles most likely result from intraparticle rearrangements. We report several experiments and develop a simplified geometric model to support this claim.…”
supporting
confidence: 87%
“…This is mostly because ligand-pore interactions have been shown to be limited for wild-type αHL in near neutral pH conditions. 28,30 In any case, our results represent a significant development in the area of cluster characterization and provide a unique tool for observing ligand-induced cluster dynamics.…”
Section: Introductionmentioning
confidence: 77%
“…In particular, it is worth noting that the salt bridges formed between the glutamic acid and lysine residues in the constriction region of the pore limit the possibility of cluster-pore interactions. 28 Our work showed that the pore is capable of monitoring previously unknown discrete transitions between physical states whose properties were dependent on ligand mass and type. We suggested that these transitions result from reorganization of the ligands on the surface of the cluster through either lateral diffusion along the surface or through ligand folding.…”
Section: Introductionmentioning
confidence: 83%
“…One challenge to develop nanopore sensors is to slow down the translocation of target analytes in the nanopore so that analyte events could be captured by the current recording technique (usually, ∼100 μs event residence time is required). In addition to taking advantage of the experimental conditions to regulate molecular and ionic transport , two major approaches have been utilized in the nanopore sensor design: one involves the structural modification of the nanopore interior to construct binding sites , while the other relies on a host or probe molecule to form host‐guest or probe‐analyte complexes . Although a wide variety of substances have been detected, nanopore detection of many small molecules, especially anions, by these two approaches is not successful.…”
Section: Methodsmentioning
confidence: 99%